BEBERAPA KENDALA IMPLEMENTASI TUGAS DAN FUNGSI KOMISI INFORMASI PROVINSI KALIMANTAN SELATAN - Tamliha Harun (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2016)
The objective of this research is to find out how the constraints faced by the Information Committee of South Kalimantan Province in the implementation of tasks and functions. This type of research: descriptive, with data collection techniques: interviews, observation, and documentation. Average data analysis used is qualitative analysis. The results showed that: found some constraints / bottlenecks in the implementation of tasks and functions of the Information Committee of South Kalimantan, namely: a. Human resources: the commissioners, secretaries, and staff sekretarit still less than the maximum, b. The amount of the available budget is relatively small and highly bureaucratic management procedures. c. Infrastructure available is limited and does not conform to the standard requirements, and d. Lack of support from the government, both politically and budget, as well as the culture of permissiveness toward public disclosure.